The formation and consequences of cholesterol-rich deposits in atherosclerotic lesions - Maxfield, Frederick R.; Steinfeld, Noah; Ma, Cheng-I J. (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases remain the leading cause of death throughout the world. Accumulation of lipoprotein-associated lipids and their interaction with macrophages are early steps in the development of atherosclerotic lesions. For decades, it has been known that aggregates of lipoproteins in the subendothelial space are found in early plaques, and these aggregates are tightly associated with extracellular matrix fibers. Additionally, most of the cholesterol in these subendothelial aggregates is unesterified, in contrast to the core of low-density lipoproteins (LDL), in which cholesteryl esters predominate. This suggests that the hydrolysis of cholesteryl esters occurs extracellularly. At the cellular level, macrophages in early plaques engage with the LDL and ingest large amounts of cholesterol, which is esterified and stored in lipid droplets. When excessive lipid droplets have accumulated, endoplasmic reticulum stress responses are activated, leading to cell death. The cholesterol-laden dead cells must be cleared by other macrophages. For many years, it was unclear how unesterified (free) cholesterol could be formed extracellularly in early lesions. Papers in the past decade have shown that macrophages form tightly sealed extracellular attachments to aggregates of LDL. These sealed regions become acidified, and lysosomal contents are secreted into these compartments. Lysosomal acid lipase hydrolyzes the cholesteryl esters, and the free cholesterol is transported into the macrophages. High concentrations of cholesterol can also lead to formation of crystals of cholesterol hydrate, and these crystals have been observed in atherosclerotic blood vessels. Characterization of this process may lead to novel therapies for the prevention and treatment of atherosclerosis.